2018
DOI: 10.2215/cjn.14261217
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Impact of Illness and Care on Patients with Advanced Kidney Disease

Abstract: Interactions with individual providers and with the wider health system coupled with patients' own struggles to make meaning of their illness can take a large emotional toll. A deeper appreciation of patients' emotional experiences may offer important opportunities to improve care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…To the best of our knowledge, this study represents the first pilot randomized trial of a video decision aid on knowledge of supportive kidney care. The landscape of care for older and frail patients with advanced CKD has changed to prioritize shared decision-making, quality of life, and better transitions of care at the end of life [50][51][52]. Our trial demonstrated that knowledge of supportive kidney care improved significantly among participants regardless of the educational intervention -this only enriches shared decision-making.…”
Section: Discussionmentioning
confidence: 75%
“…To the best of our knowledge, this study represents the first pilot randomized trial of a video decision aid on knowledge of supportive kidney care. The landscape of care for older and frail patients with advanced CKD has changed to prioritize shared decision-making, quality of life, and better transitions of care at the end of life [50][51][52]. Our trial demonstrated that knowledge of supportive kidney care improved significantly among participants regardless of the educational intervention -this only enriches shared decision-making.…”
Section: Discussionmentioning
confidence: 75%
“…Because our study relied on patientreported difficulty with adherence by social worker assessment, the length and quality of the relationship between social worker and patient (which are likely to be short and low at the initial assessment at the clinic), or problems with general mistrust of the medical system, could affect patient responses. 18 In addition, social desirability bias could cause patients to underreport difficulty in adherence, with the hope of being viewed favorably by the social worker. 19 Importantly, patients only reported difficulty with adherence to recommendations, and it is possible that patients are non-adherent for reasons other than finding them difficult.…”
Section: Discussionmentioning
confidence: 99%
“… 62 , 65 - 67 There is a large emotional toll associated with having CKD, especially when it comes to deciding on and initiating dialysis. 38 , 49 , 68 Anxiety, depression, and the emotional impact of dialysis are additional patient quality metrics that must be incorporated into CKD guidelines as they have been shown to predict patient morbidity, mortality, and QOL. 62 Psychologists are considered an essential part of any multidisciplinary RRT educational program.…”
Section: Reviewmentioning
confidence: 99%
“… 47 Therefore, it is important to ask what CKD means to them, how it has affected their lifestyle and family, and what support structures they have. 47 , 68 …”
Section: Reviewmentioning
confidence: 99%